Factors Affecting The Performance of Accounting Information Systems with Gender as a Moderating Variable - Neni Nurhayati (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine and analyze the effect of AIS user satisfaction, AIS personal technical ability, training and education of AIS users on AIS performance with gender as a moderating variable in all offices in Kuningan Regency either simultaneously or partially. The research method used is descriptive and verification methods. The research population is in all offices in Kuningan Regency as many as 18 offices in Kuningan Regency. Calculation of the sample using the slovin formula so that the sample is obtained as many as 74 respondents. Then the sampling was carried out using probability sampling technique with simple random sampling technique. The data collection technique uses a questionnaire distributed to all offices in Kuningan Regency, while the data analysis technique uses multiple regression analysis and moderate regression analysis (MRA). The results showed that AIS user satisfaction, AIS personal technical ability, training and education of AIS users had a simultaneous and significant effect on AIS performance. AIS user satisfaction, AIS personal technical ability, training and education of AIS users partially have a positive and significant effect on AIS performance. Gender moderates the effect of AIS user satisfaction, AIS personal technical ability, training and education of AIS users on AIS performance.